On some perturbation techniques for quasi-linear parabolic equations. (1990) - Malyshev, Igor
Abstract : We study a nonhomogeneous quasi-linear parabolic equation and introduce a method that allows us to find the solution of a nonlinear boundary value problem in explicit form. This task is accomplished by perturbing the original equation with a source function, which is then found as a solution of some nonlinear operator equation.